Business Environment in Kazakhstan: Assessing Infrastructure Availability - D. Z. Rakhmatullayeva; T. V. Kudasheva; D. A. Kaldiyarov; R. U. Urinboyev; A. B. Khajiyeva (Экономика: стратегия и практика, 2024)
The study aims to quantitatively assess the availability of various infrastructures for doing business and identify the main barriers in the infrastructure industry that hinder the ease of doing business and investment development in regions of Kazakhstan. The authors assessed infrastructure accessibility in Kazakhstan's regions based on an SME managers' survey. They developed an index of infrastructure availability, a practical tool for gauging infrastructure development in a specific region or country. This index is crucial for investment planning and developing relevant sectors of the national economy. The findings revealed that no region in Kazakhstan has a good infrastructure. Access to its most essential types is only at an average level, with the lowest index values observed in Almaty and East Kazakhstan regions. The analysis of SMEs' problems with access to infrastructure highlighted bureaucracy and difficulties in obtaining permits, high wear and tear of networks, and high connection costs as the main issues. The authors underscore the increasing global economic and geopolitical risks that lead to fundamental changes in Central Asia, particularly Kazakhstan, which has excellent potential for developing transit routes between East and West. They advocate for active investment in infrastructure projects as a solution. According to expert forecasts, if Kazakhstan invests at least 4% of its GDP annually, it can completely replace and modernize the republic's worn-out transport infrastructure by 2040, leading to significant economic benefits. The authors will use the study's results to create regional indices of doing business in Kazakhstan.